Assessment of the Environmental Impact of Grazing in Mahjouz al-Mustawī Using Remote Sensing Techniques and Geographic Information Systems (The International Journal for Scientific Research, 2026)
This study aimed to understand and analyze the environmental impact of grazing in the Mahjouz Al-Mustawe pastures using remote sensing techniques and geographic information systems. Environmental and analytical methodologies were employed to understand the nature of the pasture’s ecosystem, applying the Normalized Difference Vegetation Index (NDVI) from 2013 to 2018 prior to the grazing ban in Mahjouz Al-Mustawe, followed by an analysis of the results of the grazing ban from 2018 to 2025 using MODIS satellite imagery on the Google Earth Engine platform. The MODIS satellite was selected for its ability to provide satellite imagery corrected for atmospheric and geometric errors, and it is particularly suited to studying changes in the environment and land cover, as it offers a specific function for the NDVI (Normalized Difference Vegetation Index). A field survey was conducted to count herd numbers using the Plot Sampling methodology, which involves dividing the area into specific plots, calculating the animal density in each plot, and then using the average to estimate the total number of herds in the pastures (J and Sutherland, 2006). We also applied the equation for calculating pasture dry matter biomass and determined production capacity accurately by taking samples from the study area in 1x1-meter plots and measuring their weight before and after drying (Rahetlah, Salgado, and Andrianarisoa, 2014) Then, applying the stocking rate formula, which helps determine the pasture’s carrying capacity for livestock and the productive capacity of the vegetation cover, thereby determining the number of livestock allowed to graze the pasture (A. Blair & H. van, 1991), as well as contributing to the inventory of the most prominent seasonal and perennial plants in the pastures.The results showed a significant positive shift in the environmental condition of the reserve following the implementation of the grazing ban; satellite analyses revealed that an area of 1,672 km² (65% of the pasture area) had entered a phase of slight improvement and recovery, while an area of 840 km² (33% of the area) showed strong indications of entering a phase of active recovery and regaining vegetation density. These results confirm the high effectiveness of environmental protection measures in restoring the vitality of natural pastures and achieving sustainable development goals in the region.
Keywords: Environmental Impact Assessment; Contour Lines; NDVI; Grazing Capacity; Pastures; Buraidah; Environmental Degradation; Google Earth